2011
DOI: 10.1128/jb.00899-10
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into Aeropyrum pernix OppA, a Member of a Novel Archaeal OppA Subfamily

Abstract: In this study we gain insight into the structural and functional characterization of the Aeropyrum pernix oligopeptide-binding protein (OppA Ap ) previously identified from the extracellular medium of an Aeropyrum pernix cell culture at late stationary phase. OppA Ap showed an N-terminal Q32 in a pyroglutamate form and C-terminal processing at the level of a threonine-rich region probably involved in protein membrane anchoring. Moreover, the OppA Ap protein released into the medium was identified as a "nicked"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The difference in sequence could mean that the proteins have different oligopeptide ligands. Oppa is usually lipid anchored in the membrane, but studies have reported that a soluble form actively binds peptides in the cytosol of other organisms ( 26 ). Our collaborators have previously noted that Methanococcus voltae (a close cousin to M. barkeri ) cells grown on FeS 2 show increased biofilm formation and clumping ( 14 ), and the proteomes of Fe(II)/HS − - and FeS 2 -grown M. barkeri have upregulated proteins related to biofilm formation and signaling.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in sequence could mean that the proteins have different oligopeptide ligands. Oppa is usually lipid anchored in the membrane, but studies have reported that a soluble form actively binds peptides in the cytosol of other organisms ( 26 ). Our collaborators have previously noted that Methanococcus voltae (a close cousin to M. barkeri ) cells grown on FeS 2 show increased biofilm formation and clumping ( 14 ), and the proteomes of Fe(II)/HS − - and FeS 2 -grown M. barkeri have upregulated proteins related to biofilm formation and signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the solution was mixed with the peptide bradykinin (RPPGFSPFR) and crystallized in order to elucidate interactions with the specific peptide rather than endogenous peptides. Bradykinin was used in peptide selectivity studies of other archaeal OppAs 16,17 …”
Section: Resultsmentioning
confidence: 99%
“…Bradykinin was used in peptide selectivity studies of other archaeal OppAs. 16,17 The structure determination by the molecular replacement method using the structure of B. subtilis OppA (PDB ID: 1XOC) 25 was unsuccessful due to low sequence identity of 14%. Structure determination by multi-wavelength anomalous dispersion or singlewavelength anomalous dispersion (SAD) methods using selenomethionine (SeMet) derivative protein was unsuccessful because most of the methionine residues may be located in the loop region according to secondary-structure prediction.…”
Section: Structure Determination Of Tkoppamentioning
confidence: 99%
See 1 more Smart Citation
“…The class of oligopeptide-binding proteins characterized in the crenarchaeal species S. solfataricus and Aeropyrum pernix contains an N-terminal secretory signal sequence with an SPase I cleavage site and an additional C-terminal transmembrane segment (Elferink et al, 2001 ; Gogliettino et al, 2010 ; Balestrieri et al, 2011 ). The membrane anchor is preceded by a stretch of glycosylated serine and threonine residues.…”
Section: Diversity Of Secreted Proteinsmentioning
confidence: 99%